2022
DOI: 10.1073/pnas.2119614119
|View full text |Cite
|
Sign up to set email alerts
|

Larger images are better remembered during naturalistic encoding

Abstract: We are constantly exposed to multiple visual scenes, and while freely viewing them without an intentional effort to memorize or encode them, only some are remembered. It has been suggested that image memory is influenced by multiple factors, such as depth of processing, familiarity, and visual category. However, this is typically investigated when people are instructed to perform a task (e.g., remember or make some judgment about the images), which may modulate processing at multiple levels and thus, may not g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 74 publications
8
31
0
Order By: Relevance
“…Here we found that face valence performance in the parafovea (4) was reduced to a greater extent with ~20% on average in the blocked-design experiment and ~27% on average in the single trial experiment. It has been suggested that cortical magnification factor 15,27 may account for reductions in performance in peripheral vision [24][25][26]28 . In line with the idea that cortical magnification contributes to peripheral performance reductions, an earlier study using bigger face stimuli (~15) found that peripheral performance for larger eccentricities (15-30) decreased with eccentricity but was overall much higher than in our study (87%-95%) 9 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we found that face valence performance in the parafovea (4) was reduced to a greater extent with ~20% on average in the blocked-design experiment and ~27% on average in the single trial experiment. It has been suggested that cortical magnification factor 15,27 may account for reductions in performance in peripheral vision [24][25][26]28 . In line with the idea that cortical magnification contributes to peripheral performance reductions, an earlier study using bigger face stimuli (~15) found that peripheral performance for larger eccentricities (15-30) decreased with eccentricity but was overall much higher than in our study (87%-95%) 9 .…”
Section: Discussionmentioning
confidence: 99%
“…The experimental session started with visual acuity [14][15][16] measurements using a logMAR chart (measurements are available for 54 of the 56 participants). This was followed by a short training session with an identical setup and conditions as that of the main experimental task (ending when reaching >= 75% accuracy; images different than those used in the main experiment were used in the training).…”
Section: General Proceduresmentioning
confidence: 99%
“…A recent study also revealed that the size of images affects our ability to remember image content during naturalistic exploration [37]. Although our study did not involve naturalistic exploration, it clearly steered participants' attention, and we made extra care that both AR and NON-AR showed comparable imagery, it would still be interesting to explore if the size of imagery has an effect on the ability to memorise vocabulary words.…”
Section: Usability and User Experiencementioning
confidence: 91%
“…Careful consideration was given to the selection of annotation and visualisation size. Previous research showed the size of images affects our ability to remember image content during naturalistic exploration [37]. However in such exploration individuals are first asked to freely explore an image without any instructions and are then asked about the details observed.…”
Section: Application Designmentioning
confidence: 99%
“…Careful consideration was given to the selection of annotation and visualisation size. Previous research showed the size of images affects our ability to remember image content during naturalistic exploration [38]. However in such exploration individuals are first asked to freely explore an image without any instructions and are then asked about the details observed.…”
Section: Application Designmentioning
confidence: 99%